Infectious risks associated with the use of propofol - Bach, Alfons; Motsch, Johann (Acta anaesthesiologica Scandinavica, 1996)
Background: Investigations of the Centers for Disease Control into postoperative infections have implicated extrinsically contaminated propofol. Methods: To evaluate the infectious risk associated with intravenous anaesthetic agents, we surveyed the literature from 1971 to 1995 using the Medline database. Papers covering infections related to intravenous anaesthetic agents were included. Results: The review of the literature on infections associated with propofol and other intravenous anaesthetics shows that this infectious risk is minimal and often caused by breakdowns in aseptic techniques. Conclusions: We conclude that, if standard hygienic precautions are taken, the risk of in-use contamination of intravenous anaesthetics is low. If strict hygienic guidelines are followed in handling propofol, this agent can be safely administered to patients.
Gesehen am 15.11.2023